Effects of variable thermal conductivity on the coupling of conduction and Joule heating with MHD free convection flow along a vertical flat plate - Nasrin, Rehena; Alim, Md. Abdul (Journal of Naval Architecture and Marine Engineering, 2011)
The effects of variable thermal conductivity on the coupling of conduction and Joule heating with MHD free convection flow along a vertical flat plate have been described by this present work. With a goal to attain similarity solutions of the problem posed, the developed equations are made dimensionless by using suitable transformations. The non-dimensional equations are then transformed into non-linear equations by introducing a non- similarity transformation. The resulting non-similar equations together with their corresponding boundary conditions based on conduction and convection are solved numerically by using the implicit finite difference method along with Keller-box scheme. Numerical results for the details of the velocity profile, temperature profile, skin friction coefficient and the surface temperature profile are shown both on graphs and tabular form for different values of the set of parameters entering into the problem. DOI: 10.3329/jname.v7i1.4322